Дослідження балочних елементів виготовлених за технологією ЗД друку - Нурманов, Артур Нурланович; Nurmanov, Artur Nurlanovych (Національний університет "Львівська політехніка", 2024)
Оскільки бетонні роботи наразі становлять одну з найдорожчих складових традиційного будівництва, впровадження технології 3D-друку у будівельний процес відкриває можливості суттєво знизити витрати та вирішити низку актуальних проблем. А саме - подолання дефіциту кваліфікованих кадрів, прискорення темпів зведення об'єктів, підвищення якості за рахунок мінімізації впливу людського чинника, скорочення обсягів відходів, зменшення вуглецевого сліду бетонного виробництва. Використання дерев’яної опалубки при проведенні бетонних робіт являється найдорожчим і найбільш трудозатратним процесом бетонування. Оскільки головними перевагами технології 3D друку є відмова від опалубки і можливість друку складних архітектурних форм, які суттєво підвищують вартість опалубочних робіт. Використання цієї технології може скоротити час будівництва на 60%, а витрати на робочу силу - на 80%. У розділі 1 здійснено аналіз наукових досліджень на тему застосування, 3D друку у будівництві. Були проаналізовані будівлі, які зведені за допомогою даної технології, опрацьовані головні переваги і виклики використання 3D принтера на будівництві, проаналізовані дослідження в напрямках розробки технології друку, оптимізації процесів, вибору складу суміші для друку, моделювання, розрахунків надрукованих конструкцій. Один із перших знакових прикладів використання технології 3D друку в будівництві відбувся в Китаї у 2015 році під час Пекінського тижня дизайну був представлений надрукований павільйон «Вулкан» [1]. У 2017 році в Нідерландах було реалізовано перший у світі велосипедний міст, виготовлений методом 3D-друку з бетону, що стало значним досягненням у галузі будівництва. Проліт мосту складає 6,5 м, а ширина 3,5 м. Висота перерізу мосту 0,92 м. Розрахункове навантаження на міст склало 5 кН/м2 [2]. Були представлені головні стратегії виготовлення конструкцій за допомогою 3D-друку і описані переваги і недоліки застосування кожної з них. Виходячи з технологічних можливостей застосування технології 3D друку можлива як на будівельному майданчику так і у павільйоні, з подальшим транспортування конструкцій, або цілої споруди на будову [3]. Були проаналізовані основні методи 3D-друку: екструзія матеріалу, стереолітографія, спікання порошкового шару, крапельне нанесення матеріалу, зв’язувальне склеювання та шарове склеювання листів [4]. Також проаналізовано принцип розрахунку балок згідно діючих нормативних документів України. [5] У розділі 2 описана методика експериментальних досліджень. Описано дослідження фізико-механічних властивостей матеріалів шляхом руйнування стандартних зразків кубиків і призм згідно нормативних документів України [6]. Описано технологічний процес виготовлення балок за допомогою технології 3D друку, представлені головні технологічні і проектні креслення. Розроблено методику випробування балки під навантаженням, описано лабораторний стенд і представлено його креслення та вигляд. Також була описана методика розрахунку залізобетонної балки. У розділі 3 описані результати дослідження. Визначено руйнівне зусилля зразків кубиків і призм. Згідно результатів експериментальних досліджень проведено еквівалентне перетворення експериментальних результатів до нормативних показників відповідного класу бетону. Були представлені результати дослідження балки під навантаженням у табличній формі. Також були складені графіки деформацій бетону та арматури. Було проведено порівняння експериментальних та теоретичних значень. У розділі 4 представлено економічне порівняння. Об’єкт дослідження: балкові конструкції, виготовлені методом 3D-друку. Предмет дослідження: параметри формування, геометрія перерізу, несуча здатність і технологічні особливості виготовлення. Мета дослідження: аналіз експериментального зразка та узагальнення наукових підходів до оптимізації конструкцій, виготовлених із застосуванням технології 3D-друку.

As concrete work is currently one of the most expensive components of traditional construction, the introduction of 3D printing technology into the construction process opens up opportunities to significantly reduce costs and solve a number of current problems. Namely, overcoming the shortage of qualified staff, accelerating the pace of construction, improving quality by minimising the impact of the human factor, reducing waste, and reducing the carbon footprint of concrete production. The use of wooden formwork in concrete work is the most expensive and labour-intensive concrete process. The main advantages of 3D printing technology are the elimination of formwork and the ability to print complex architectural shapes, which significantly increase the cost of formwork. The use of this technology can reduce construction time by 60% and labour costs by 80%. Chapter 1 analyses scientific research on the application of 3D printing in construction. It analyses buildings constructed using this technology, discusses the main advantages and challenges of using a 3D printer in construction, and analyses research in the areas of printing technology development, process optimisation, selection of the composition of the printing mixture, modelling, and calculations of printed structures. One of the first significant examples of the use of 3D printing technology in construction took place in China in 2015, when the printed Volcano pavilion was presented during Beijing Design Week [1]. In 2017, the world's first 3D printed concrete bicycle bridge was built in the Netherlands, which was a significant achievement in the construction industry. The bridge span is 6.5 m and the width is 3.5 m. The cross-sectional height of the bridge is 0.92 m. The design load on the bridge was 5 kN/m2 [2]. The main strategies for manufacturing structures using 3D printing were presented and the advantages and disadvantages of each of them were described. Based on the technological capabilities, 3D printing technology can be used both at the construction site and in the pavilion, with the subsequent transport of structures or the entire structure to the construction site [3]. The main 3D printing methods were analysed: material extrusion, vat photopolymerization, powder bed fusion, droplet material deposition, binder jetting and layered sheet jetting [4]. The method of beams calculation according to the current regulatory documents of Ukraine is also analysed. [5] Chapter 2 describes the methodology of experimental research. The research of physical and mechanical properties of materials by fracturing standard cubes and prisms in accordance with the regulatory documents of Ukraine [6] is described. The technological process of manufacturing beams using 3D printing technology is described, and the main technological and design drawings are presented. The methodology for testing a beam under load is developed, the laboratory bench is described, and its drawings and appearance are presented. The method of calculation of a reinforced concrete beam was also described. Chapter 3 describes the results of the research. The destructive strain of cube and prism specimens was determined. According to the results of the experimental research, an equivalent transformation of the experimental results to the normative parameters of the relevant class of concrete was carried out. The results of the research of the beam under load were presented in tabular form. The deformation graphs of concrete and reinforcement were also drawn. The experimental and theoretical values were compared. Chapter 4 presents an economic comparison. Object of research: beam structures made by 3D printing. Subject of research: moulding parameters, cross-sectional geometry, bearing capacity and technological features of manufacturing. Purpose of the study: to analyse an experimental sample and generalise scientific approaches to optimising structures made using 3D printing technology.
Research of beam elements manufactured using 3D printing technology
Keywords: 3.192.00.00; 3D-друк; цифрове будівництво; балка; зчеплення шарів; армування; технологічне формування. СПИСОК ВИКОРИСТАНИХ ДЖЕРЕЛ 1. Gavrylyuk S.A.; New technologies in the field of construction. Using 3d printers Academic Journals and Conferences. ITBP.2021. p. 15-22. 11. Hamidreza Gh.S.; Corker J.; Fan M 2. Salet; T. A. M.; Ahmed; Z. Y.; Bos; F. P.; Laagland; H. L. M. Design of a 3D printed concrete bridge by testing. Virtual and Physical Prototyping. Vol.13(3). 2018. P. 222–236. 3. Placzek; G.; & Schwerdtner; P. (2024). A Global Snapshot of 3D-Printed Buildings: Uncovering Robotic-Oriented Fabrication Strategies. Buildings; 14(11); 3410. https://doi.org/10.3390/buildings14113410 4. Nesterenko; P. N. (2020). 3D printing in analytical chemistry: current state and future. Pure and Applied Chemistry; 92(8); 1341–1355. https://doi.org/10.1515/pac-2020-0206 5. ДСТУ Б В.2.6-156:2010 Конструкції будинків і споруд. Бетонні та залізобетонні конструкції з важкого бетону. Правила проектування. Мінрегіонбуд.2011 6 ДСТУ Б В.2.7-214:2009 Будівельні матеріали. Бетони. Методи визначення міцності за контрольними зразками. Мінрегіонбуд 2009; 3D printing; digital construction; beam; layer adhesion; reinforcement; technological moulding. REFERENCES 1. Gavrylyuk S.A.; New technologies in the field of construction. Using 3d printers Academic Journals and Conferences. ITBP.2021. p. 15-22. 11. Hamidreza Gh.S.; Corker J.; Fan M 2. Salet; T. A. M.; Ahmed; Z. Y.; Bos; F. P.; Laagland; H. L. M. Design of a 3D printed concrete bridge by testing. Virtual and Physical Prototyping. Vol.13(3). 2018. P. 222–236. 3. Placzek; G.; & Schwerdtner; P. (2024). A Global Snapshot of 3D-Printed Buildings: Uncovering Robotic-Oriented Fabrication Strategies. Buildings; 14(11); 3410. https://doi.org/10.3390/buildings14113410 4. Nesterenko; P. N. (2020). 3D printing in analytical chemistry: current state and future. Pure and Applied Chemistry; 92(8); 1341–1355. https://doi.org/10.1515/pac-2020-0206 5. DSTU B B.2.6-156:2010 Structures of buildings and structures. Concrete and reinforced concrete structures of heavy concrete. Design rules. Minregionbud.2011 6 DSTU B B.2.7-214: 2009 Construction materials. Concretes. Methods for determination of strength by control samples. Minregionbud 2009